Approaches to Ibāḍī Exegetical Tradition - Albayrak, İsmail (Harrassowitz Verlag, 2020)
Cover -- Contents -- Preface -- Chapter One: Ibāḍī Tafsīr, A Historical Survey -- 1.1 Introduction -- 1.2 Tafsīr as a Genre -- 1.3 Some Preliminary Remarks on Ibāḍī Tafsīr -- 1.4 Ibāḍī Tafsīr (Exegetical Works). -- 1.5 Non-Ibāḍīs' Depiction of Ibāḍī Tafsīr -- 1.6 Tafsīr in Accordance With Ibāḍī Scholars -- 1.7 General Ibāḍī Tafsīr Works -- 1.7.1 The Formative Period -- 1.7.2 Ibāḍī Exegeses in the Classical Period -- 1.7.3 Modern Exegesis -- 1.7.4 Conclusion -- Chapter Two: The Ibāḍī Approach to the Methodology ofQur'anic Exegesis -- 2.1 Introduction -- 2.2 Ibāḍī Perceptions of the Revelation and the Qur'an -- 2.2.1 Khalq al-Qurʾān -- 2.2.2 Jamʿ al-Qurʾān (Collection of the Qur'an -- 2.2.3 'Seven Letters' (Sabʿat al-Aḥruf) and Variant Readings -- 2.3 ʿUlūm al-Qurʾān (Disciplines of Qur'anic Knowledge) -- 2.3.1 Asbāb al-Nuzūl (Occasions of Revelation). -- 2.3.2 Qur'anic Narratives, Amthāl and Isrāʾīliyyāt -- 2.3.3 Tanāsub (Thematic and Structural Unity AmongQur'anic Sūras and Verses) -- 2.3.4 Naskh (Abrogation) -- 2.3.5 Muḥkam and Mutashābih (Clear and Ambiguous Verses) -- 2.4 Conclusion -- Chapter Three: 'Other' Among Us: The Perception of Khārijite andIbāḍī Islam in the Muslim Exegetical Traditions -- 3.1 Introduction -- 3.2 The Perception of the Khārijites and the Ibāḍīsin Classical Qur'anic Exegesis -- 3.2.1 Perspectives on the Khārijites' and Ibāḍīs' Interpretation of the Qur'an -- 3.2.2 The Critique of Khārijite Jurisprudence -- 3.2.3 The Critique of the Khārijites' Kalām (Theology) -- 3.3 Conclusion -- Chapter Four: Re-Evaluation of the Notion of Jesus' Return inIbāḍī Exegetical Tradition -- 4.1 Introduction -- 4.2 General Approaches to the Notion of Nuzūl ʿĪsā in Ibāḍī Scholarship -- 4.3 Aṭfayyish and the Notion of Nuzūl ʿĪsā -- 4.4 Post-Aṭfayyish Approaches to the Notion of Nuzūl ʿĪsā.